The Influence of Local Revenue and Transfer Funds on Regional Expenditure in the City of Jayapura in 2014-2023 - Negeru Kogoya; Endarwati Endar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of Local Own-Source Revenue (PAD) and Transfer Funds on Regional Expenditures in Jayapura City from 2019 to 2023. The research employs a quantitative approach using multiple linear regression analysis to assess the relationship between the independent variables (PAD and Transfer Funds) and the dependent variable (Regional Expenditures). The results indicate that PAD and Transfer Funds significantly impact regional expenditures individually and simultaneously. The findings suggest that while Jayapura City has experienced growth in PAD, it remains heavily reliant on transfer funds from the central government. This study provides insights for policymakers to enhance fiscal independence by optimizing local revenue sources and ensuring effective allocation of transfer funds for regional development.